Controversies in Choledochal Malformations: A Survey among Dutch Pediatric Surgeons - van den Eijnden, Maria Hendrina Antoinette; de Kleine, Ruben H.; Verkade, Henkjan J.; Wilde, Jim C. H.; Peeters, Paul M. J. G.; Hulscher, Jan B. F. (European Journal of Pediatric Surgery, 2015)
Background Choledochal malformation (CM) is a rare medical condition of which 80% are diagnosed in pediatric patients. There are several important controversies regarding diagnostic workup, management, and follow-up in these pediatric patients. To assess preferences and practices of Dutch pediatric surgeons regarding the diagnostic procedures, management, and follow-up of children with CM we conducted an electronic survey.Methods A questionnaire was sent to all the pediatric surgeons working in the academic centers and the only community hospital with a pediatric surgery service. The questionnaire included, items regarding incidence, diagnostic workup, interval between diagnosis and surgery, surgical techniques, and follow-up. We also assessed whether personal exposure influenced the preferences and practices.Results Overall 22 out of the 31 (71%) Dutch pediatric surgeons returned the questionnaire. Total 15 out of 22 (68%) encountered CM up to 2 times/y, whereas 7 out of 22 (32%) encountered it more than 2 times/y. Indications for surgery were significantly different between surgeons who encountered CM > 2 time/y versus those who did not: 6/6 (100%) of surgeons encountering CM > 2 times/y considered the presence of an asymptomatic CM an indication for surgery versus 5/14 (36%) of the pediatric surgeons who encountered a CM up to 2 times/y (p = 0.01). Overall 12 out of the 22 (55%) respondents preferred surgery between 6 months and 2 years of age. The amount of exposure did not differ in preferred age at surgery or surgical technique. In the symptomatic child 10/22 (45%) of respondents preferred surgery within 3 months. Overall 7/22 (32%) favored laparoscopic resection. Hepaticojejunostomy with Roux-en-Y reconstruction was the preferred reconstruction for all the respondents. One-third stated that they never performed a parenchyma resection. Follow-up was limited to 10 years in almost half of the respondents.Conclusion Dutch pediatric surgeons demonstrate a wide variety of opinions regarding diagnostic workup, treatment, and follow-up of CM. While most surgeons encounter CM up to 2 times/y, there is an association between exposure and several of the outcome parameters. Some of the answers are not in line with the expert opinion. This demonstrates that there is a need for evidence-based (inter)national guidelines regarding the diagnostic approach, management, and follow-up.
Keywords: choledochal malformation; choledochal cysts; controversies in choledochal malformation; malformation